PENGARUH PENINGKATAN JUMLAH PEMBAWA PESAN TERHADAP TINGKAT KOGNITIF RESPONDEN PADA MEDIA AUDIO - Setiadi Umar; Agus Hasan Pura P.A (Bina Ekonomi, 2009)
In the advertising, a certain style of executing messages can be encountered based on testimonial evidence. As regards testimonial evidence, the marketing party involved can employ several endorsers or make use of only one in advertisements to deliver the message.  The focus of study  is on the extent  to which people's  cognitive response are affected by an increase  in the number of endorsers  and by the differentiation  in the perceived quality of the commercials  presented  in audio-based  commercials,  a type of commercial  that can only be heard by  the respondents  who cannot  see  the actual  speaker's face.